Realization Of Farming Communities on Climate Crisis - Sukumaran, N. (Journal of Neonatal Surgery, 2025)
Realization of farming communities in the context of the climate crisis involves recognizing the profound challenges these communities face due to climate change and understanding how these impacts affect their livelihoods, food security, and overall resilience. The present research paper is an attempt to disclose the manifestations of the most important bio-spherical problem. Climate change is impact on lives and livelihood and ecological wealth. For this purpose the researcher collected the data from the agricultural communities of climate change, loss and damage on their livelihood and coping strategies for the stability of climate and preserving and conserving balanced ecosystem